Possibilities of using silicate rock powder: An overview - Ramos, Claudete Gindri (2021)
This study evaluates the on use of crushed rocks (remineralizers) to increase soil fertility levels and which contributed to increase agricultural productivity, recovery of degraded areas, decontamination of water, and carbon sequestration. The use of these geological materials is part of the assumptions of rock technology and, indirectly, facilitates the achievement of sustainable development goals related to soil management, climate change, and the preservation of water resources. Research over the past 50 years on silicate rocks focused on soil fertility management and agricultural productivity. More recently, the combined use with microorganisms and organic correctives have shown positive results to mitigate soil degradation; to expand carbon sequestration and storage; and to contribute to the adsorption of contaminants from water and soil. In this article we show results obtained in several countries and we show that this technology can contribute to the sustainability of agriculture, as well as to reverse global warming. Although mineral nutrients are released more slowly from these types of inputs, they remain in the soil for a longer time, stimulating the soil biota. In addition, they are a technology to soluble synthetic fertilizers replace, since the few nutrients derived from such inputs not consumed by plants are lost by leaching, contaminating groundwater and water resources. In addition, conventional methods rely heavily on chemical pesticides which cause damage to soil's microfauna (responsible for the decomposition of organic matter and nutrient cycling) and the loss of organic carbon (in the form of dioxide), which is quickly dispersed in the atmosphere. Silicate rock powders are applied in natura, have long-lasting residual effects and reduce greenhouse gas emissions.